Symptoms of the Planetary Condition : A Critical Vocabulary - Bunz, Mercedes; Mara Kaiser, Birgit; Thiele, Kathrin; Bunz, Mercedes; Mara Kaiser, Birgit; Thiele, Kathrin (meson press, 2017)
This book explores the future of critique in view of our planetary condition. How are we to intervene in contemporary constellations of finance capitalism; climate change and neoliberalism? Think we must! To get to the symptoms; the book$1 (Bs 38 terms ranging from affect and affirmation to world and work provide the reader with a critical toolbox to be continued. Negativity; judgment and opposition as modes of critique have run out of steam. Critique as an attitude and a manner of enquiry has not.s
English
Keywords: Philosophy; Critical Theory; Humanities; Critique; Politics; Technology; Globalization; Literature